Culture in Biblical Interpretation: The Use of Yoruba Cultural Elements in Adamo’s African Cultural Hermeneutics - Dada, Kunle (Old Testament essays, 2021)
African Cultural Hermeneutics is an approach in biblical interpretation that makes African socio-cultural context a subject of interpretation. This article shows how Adamo has deployed effectively Yoruba cultural elements in the development of this interpretative grid. This is done with a view to determining the extent to which he has engaged successfully the biblical text in a way that has translated to a better understanding of the Bible in Africa. A descriptive approach is adopted as the basic methodology for the article. Yoruba cultural archival resources such as traditions, songs, oracles, folklores and incantations (potent words) are appropriated to make the Bible come alive and relevant. For Adamo, these traditional resources have helped to elucidate the Bible and make its message meaningful for its average reader in Africa. Employing African cultural elements in the interpretative process should however be done with some measured caution. https://doi.org/10.17159/2312-3621/2021/v34n2a7